Extraction of aluminium surface energies from slab calculations: perturbative and non-perturbative approaches - Fiolhais, Carlos (2003)
Surface energies of aluminium ((1 1 1), (1 1 0) and (1 0 0)) were calculated in second-order perturbation theory based on the jellium model, and by full atomistic models using a Gaussian basis set, in the framework of density functional theory. In both cases, surface energies were extracted from slab calculations using the incremental method, which considers two slabs with consecutive numbers of layers (6 and 7 layers). In the non-perturbative calculation, the fitting method which involves a series of slabs up to 10 layers is also used to examine the limitations of the incremental method and to improve it. Our results are compared with those from other authors and with experiment being the limitations of the perturbative method discussed. The predictions of the stabilized jellium model are also referred to.